Signing Ceremony Letter of Intent (LoI) Between UMK and Alibaba Intime Commercial Group Co., Ltd., China - Universiti Malaysia Kelantan, Perpustakaan (2025)
Signing Ceremony Letter of Intent (LoI) Between UMK and Alibaba Intime Commercial Group Co., Ltd., China telah diadakan di American Corner, PPI, UMK Bachok